The International Conference on Intelligent Biology and Medicine (ICIBM) 2018: genomics meets medicine - Degui Zhi; Zhongming Zhao; Fuhai Li; Zhijin Wu; Xiaoming Liu; Kai Wang (BMC, 2019)
Abstract During June 10-12, 2018, the International Conference on Intelligent Biology and Medicine (ICIBM 2018) was held in Los Angeles, California, USA. The conference included 11 scientific sessions, four tutorials, one poster session, four keynote talks and four eminent scholar talks that covered a wide range of topics ranging from 3D genome structure analysis and visualization, next generation sequencing analysis, computational drug discovery, medical informatics, cancer genomics to systems biology. While medical genomics has always been a main theme in ICIBM, this year we for the first time organized the BMC Medical Genomics Supplement for ICIBM. Here, we describe 15 ICIBM papers selected for publishing in BMC Medical Genomics.